1981
DOI: 10.2323/jgam.27.435
|View full text |Cite
|
Sign up to set email alerts
|

Decay of coconut fibres by soil microorganisms.

Abstract: The influence of pH, temperature and organic matter on the degradation of the lignin-cellulose complex of coconut fibres was studied. Many fungi (deuteromycetes and ascomycetes) and bacteria were isolated from partly decayed coir. The decomposition of the coconut fibres by these isolates was estimated, imitating field conditions. Some fungi of the genera tested were able to partly decompose the coconut fibres after long incubation periods. However, the quick and total decay of the coir wrapper around drain pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Being relatively cheap, "cocos" soon dominated the market because high quality peat litter became scarce and expensive (Meijer 1973). At a later stage it was discovered that coconut fiber was also subject to microbiological decay (Meijer and Knops 1977;Antheunisse 1979Antheunisse , 1980Antheunisse , 1981, stimulating the drive to replace organic substances with synthetic alternatives. It was argued that, contrary to organic envelopes, synthetic ones could be manufactured according to design criteria that could be established in laboratory tests (Stuyt 1992a).…”
Section: Prewrapped Loose Materialsmentioning
confidence: 99%
“…Being relatively cheap, "cocos" soon dominated the market because high quality peat litter became scarce and expensive (Meijer 1973). At a later stage it was discovered that coconut fiber was also subject to microbiological decay (Meijer and Knops 1977;Antheunisse 1979Antheunisse , 1980Antheunisse , 1981, stimulating the drive to replace organic substances with synthetic alternatives. It was argued that, contrary to organic envelopes, synthetic ones could be manufactured according to design criteria that could be established in laboratory tests (Stuyt 1992a).…”
Section: Prewrapped Loose Materialsmentioning
confidence: 99%
“…An experiment was carried out in Erlenmeyer flasks of 500 ml capacity as described by ANTHEUNISSE (1). Each flask containing from bottom to top, water, air, coconut fibres and approximately 100 g soil (a mixture of clay and sandy soil of 1: 1; pH 7.2) was sterilized and inoculated with a fungus that may partly decompose the lignin-cellulose complex (11) and with the basidiomycete Trametes versicolor (L. ex Fr.) Lloyd CBS 47172 (T15).…”
Section: Methodsmentioning
confidence: 99%
“…In a laboratory scale experiment Antheunisse (1979) showed that coir is highly resistant to decomposition under anaerobic condition. The influence of the pH on coir degradation within the limits of 4.3 -8.0 has been reported to be either small or absent (Antheunisse, 1981).…”
Section: Coir Fibrementioning
confidence: 99%